Early recovery of interhemispheric functional connectivity after corpus callosotomy. (14th May 2019) - Hung, Sheng‐Che; Lee, Cheng‐Chia; Chen, Hsin‐Hung; Chen, Chien; Wu, Hsiu‐Mei; Lin, Ching‐Po; Peng, Syu‐Jyun
Abstract: Objective: To investigate whether interhemispheric functional connectivity (FC) recovers in the first year after total callosotomy. Methods: Eight epilepsy patients undergoing total callosotomy were recruited. Resting‐state functional magnetic resonance imaging was acquired before and after surgery. The precallosotomy and postcallosotomy interhemispheric and intrahemispheric FC was analyzed by using graph theory and voxel‐mirrored homotopic connectivity (VMHC). The seizure outcome was scored using the Engel surgical outcome scale. Results: After callosotomy (mean postoperative interval = 4 months), the network density, average node degree, characteristic path length, and global efficiency of the whole interhemispheric networks were significantly decreased, compared to those in the precallosotomy networks. However, postcallosotomy interhemispheric FC and homotopic VMHC were not significantly reduced in bilateral frontal and temporal lobes. The network density and average node degree of the intrahemispheric networks were significantly increased. The characteristic path length and global efficiency of intrahemispheric networks were unchanged. Significance: The interhemispheric FC may be preserved or recover early within the first postoperative year after total callosotomy, particularly in the frontal and anterior temporal lobes.